PERLINDUNGAN HUKUM HAK MILIK ATAS TANAH DALAM HAL TERJADI GUGATAN OLEH PIHAK LAIN (STUDI PUTUSAN MAHKAMAH AGUNG NO. 1820 K/PDT/2017) - Novia Gunawan; Endang Pandamdari (Jurnal Hukum Adigama, 2019)
Land is the surface of the earth that has various kinds of rights, one of which is land ownership rights. Land rights are rights granted by the State so that they can be granted by Indonesian citizens by way of land registration. Land registration is carried out to provide legal certainty and protection for every landowner. Although a land registration application has been made, when the petition is still submitted to a land dispute, such as an overlapping certificate, or a counterfeit certificate. Supreme Court Decision No. 1820 K / Pdt / 2017, namely the issuance of two certificates of ownership on the same land. By looking at the buying and selling procedures carried out by the parties to the Decision of the Supreme Court No. 1820 / K / Pdt / 2017, the sale and purchase has been validly carried out between the parties, then guarantees the law for Yuni and others who make the same policy only by submitting a claim to the district court where the land is located, and also as the land owner from payment of land proposal before buying and transferring land disputes by checking land certificates to the National Land Agency.